Implementasi Pembelajaran SKI Dalam Membangun Aktivitas Literasi Siswa MAS Hidayah - Anggriani, Putri (Journal of Sustainable Education, 2025)
This study aims to describe the impelementation of Islamic Cultural History ( SKI ) learning in developing students literacy at MAS Hidayah. The research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using Miles & Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that SKI learning implemented by teachers has integrated literacy activities such as reading historical texts, engaging in discussions and writing reflections. These activities enhanced students literacy skills, particularly in critical reading, analytical thinking, and written expression. Nevertheless, several challenges were indentifed, including low reading interest among some students, limited availability of Islamic history reading materials, and insufficient instructional time. Thus, SKI learning plays a strategic role in fostering students literacy when supported by innovative teaching strategies and adequate learning resources.